Desain Litter Catcher Menggunakan Metode Quality Function Deployment (QFD) Dan Analytical Hierarchy Process (AHP) - Reihan Fahrezi; Herisiswanto Herisiswanto; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
According to the observation the majority of people who dump garbage alongside the road, they throw it away from the vehicle. In this research designed a waste bin that can facilitate people who use vehicles to dispose of waste without having to get off the vehicle. In this research employed the Quality Function Deployment (QFD) method and the selection of alternatif designs using Analytical Hierarchy Process (AHP), Based on the results of open questionnaires, there were six voice of customer, which become parameters in litter catcher design that was easy to be emptied, according to standard, plastic trash writing on trash bin body, material of metal, box shape and easy to clean. Priority technical characteristics based on importance level were design with value of 27.72, finishing with value of 25.74 and construction with value of 23.76. The optimal design was chosen the alternatif design number 2 with a weight of 0.672 and CR 0.05 where the pairwise ratio that was expressed consistent.Keywords: Litter Catcher, Quality Function Deployment, Analytical Hierarchy Process